Keefektifan Model Discovery Learning berbantuan Media PAKULUS terhadap Pemahaman Konsep Matematis - Koestanti, Jeny; Ermawati, Diana; Santoso, Denni Agung (Universitas Ngudi Waluyo, 2026)
The monotonous and conventional learning process through lecture methods can cause a low understanding of students' concepts. These problems were found in grade IV students of SD 2 Kaliwungu, especially in the material on measuring the area of flat buildings. This study aims to determine the effectiveness of the PAKULUS media-assisted Discovery learning model in improving students' understanding of mathematical concepts. The Discovery learning model emphasizes the active involvement of students in discovering concepts through meaningful learning experiences, while PAKULUS media is a two-dimensional media in the form of a rectangular board equipped with flat building images to help visualize broad concepts. This study uses a quantitative approach with a pre-experiment method and a one-group pretest-posttest design. The research subjects amounted to 19 grade IV students who participated in learning for five meetings. The data collection technique uses tests and documentation. Data analysis was carried out through normality tests, paired sample t-tests, and N-gain tests. The results showed a significance value (2-tailed) < 0.05 (0.001 < 0.05), so there was a significant difference between the pretest and posttest values after treatment. The N-gain value of 0.65 is in the medium category. Thus, the PAKULUS media-assisted Discovery learning model is effective in improving the understanding of mathematics concepts of grade IV students of SD 2 Kaliwungu on the material of measuring the area of flat buildings. Abstrak Proses pembelajaran yang monoton dan konvensional melalui metode ceramah dapat menyebabkan rendahnya pemahaman konsep peserta didik. Permasalahan tersebut ditemukan pada peserta didik kelas IV SD 2 Kaliwungu, khususnya pada materi pengukuran luas bangun datar. Penelitian ini bertujuan untuk mengetahui efektivitas model Discovery learning berbantuan media PAKULUS dalam meningkatkan pemahaman konsep matematika peserta didik. Model Discovery learning menekankan keterlibatan aktif peserta didik dalam menemukan konsep melalui pengalaman belajar yang bermakna, sedangkan media PAKULUS merupakan media dua dimensi berbentuk papan persegi panjang yang dilengkapi gambar bangun datar untuk membantu visualisasi konsep luas. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pre-eksperimen dan desain one group pretest-posttest. Subjek penelitian berjumlah 19 peserta didik kelas IV yang mengikuti pembelajaran selama lima pertemuan. Teknik pengumpulan data menggunakan tes dan dokumentasi. Analisis data dilakukan melalui uji normalitas, uji paired sample t-test, dan uji N-gain. Hasil penelitian menunjukkan nilai signifikansi (2-tailed) < 0,05 (0,001 < 0,05), sehingga terdapat perbedaan yang signifikan antara nilai pretest dan posttest setelah perlakuan. Nilai N-gain sebesar 0,65 berada pada kategori sedang. Dengan demikian, model Discovery learning berbantuan media PAKULUS efektif dalam meningkatkan pemahaman konsep matematika peserta didik kelas IV SD 2 Kaliwungu pada materi pengukuran luas bangun datar.